â€Implementasi Program Nasional Pemberdayaan Masyarakat (PNPM) Mandiri Perdesaan di Kecamatan Sumber Kabupaten Rembang (Studi Kasus pada Unit Pengelola Kegiatan Kecamatan Sumber)â€ - Juni Liana, Ike Elissa; Hidayat, Zainal; Marom, Aufarul (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2015)
The most important stage in a process of public policy is policy implementation. One of the government programs to reduce poverty in the villages on the basis of community empowerment is PNPM Mandiri. Activity Management Unit (UPK) is one of the most important component in the success of PNPM Rural destination. But over PNPM Rural in Sub Source, former Secretary of the District of Sumber stumble UPK corruption cases womenâ€Ÿs credit funds (SPP). As a result of this case is the amount of arrears by a group of women beneficiaries SPP funds. The purpose of this study is to investigate the implementation of PNPM Rural in District Related resources on UPK District of Sumber and to identify factors driving and inhibiting factors of implementation. The theory used is the implementation of the theory of George Edwards III. This research is a qualitative descriptive study.Informants in this study is the Chairman of the Supervisory Board UPK District of Sumber, Chairman and Treasurer UPK District of Sumber and Chairman of user groups womenâ€Ÿs credit fund. This research data collection techniques are not structured interviews, observation, documentation and triangulation of data sources. To analyze the data using domain analysis to analyze the general picture of the research object. The result showed that the implementation of Rural seen in District Sumber of policies considered good accuracy, precision of execution is considered less good, the precision of the target is considered good, the environment is considered good accuracy and precision of the process is considered less good. While driving factor is the implementation of communication and resources.While limiting factor is the implementation of dispotion, beraucratic structures and the level of commitment of the target group.